(untitled) (The Peerian Journal, 2025)
The research aims to highlight the challenges facing tourism policy in Iraq and the role of tourism media in overcoming these challenges. The researcher began this work to identify ways to solve the crises, obstacles, and difficulties that hinder the implementation of tourism policies in Iraq. The study also seeks to produce results and recommendations that help achieve the objectives of this research